V-Care Application Design Using Design Thinking Method - Hakim, Ghaeril Juniawan Parel; Saputra, Fikri; Ardhani, Muhammad Naufal; Fami, Amata; Barus, Irma Rasita Gloria (PPM Telkom University, 2024)
This research aims to develop